A simple decision rule including D‐dimer to reduce the need for computed tomography scanning in patients with suspected pulmonary embolism. (19th June 2015) - van Es, J.; Beenen, L. F. M.; Douma, R. A.; den Exter, P. L.; Mos, I. C. M.; Kaasjager, H. A. H.; Huisman, M. V.; Kamphuisen, P. W.; Middeldorp, S.; Bossuyt, P. M. M.
Summary Background An 'unlikely' clinical decision rule with a negative D‐dimer result safely excludes pulmonary embolism (PE) in 30% of presenting patients. We aimed to simplify this diagnostic approach and to increase its efficiency. Methods Data for 723 consecutive patients with suspected PE were analyzed (prevalence of PE, 22%). After constructing a logistic regression model with the D‐dimer test result and items from the Wells' score, we identified the most prevalent combinations of influential items and selected new D‐dimer positivity thresholds. The performance was separately validated with data from 2785 consecutive patients with suspected PE. Results Three Wells items significantly added incremental value to the D‐dimer test: hemoptysis, signs of deep vein thrombosis and 'PE most likely'. Based on the most frequent combinations of these three items, we identified two groups: (i) none of these three items positive (41%); (ii) one or more of these items positive (59%). When applying a 1000 μg/L D‐dimer threshold in group 1 and 500 μg/L in group 2, PE could be excluded without CT scanning in 36%, at a false‐negative rate of 1.2% (95%, 0.04‐3.3%). In the validation set, these proportions were 46% and 1.9% (95% CI, 1.2‐2.7%), respectively. Using the conventional Wells score with a normal D‐dimer result, these rates were, respectively, 22% and 0.6% (95% CI, 0.10‐2.4%). Conclusion Combining Wells items with the D‐dimer test resulted in a simplified decision rule, which reduces the need for CT scanning in patients with suspected PE. A prospective validation is required before it can be implemented in clinical practice.